In Vitro evaluation of T- cell Acute Lymphoblastic Leukemia cell line response to a combination of dual anticancer agent: SRJ23 and Hydroxyurea - Khalid, Bahariah; Karuppiah, Thilakavathy; Stanslas, Johnson; Marashdeh, Laith (2024)
T-cell acute lymphoblastic leukemia (T-ALL) is a hostile haematologic neoplasm caused by a malignant transformation of immature progenitors of T-cells. Due to the variable response to conventional chemotherapy regimens available to-date, a holistic chemotherapy combination drugs with greater precision to obtain the desired results are worth studying. We aim to evaluate the inhibitory effect of a readily available cyto-reducing agent, hydroxyurea (HU) with SRJ23, on Jurkat cell line which are an immortalised of human T lymphocyte cells to determine the efficacy in vitro.